Does Psychological Ownership of Knowledge Matter? Servant Leadership and Knowledge Hiding in Organizations: AProposed Framework - Gabriel Oyebanjo OGUNLELA (Journal of Economics and Behavioral Studies, 2018)
Knowledge hiding can have many adverse effects on organizational development, and it is consequently important to look at its various causes, and also the impact such activities haveon targets, perpetrators, and organizations as a whole. Various studies investigate the effects of knowledge hiding on organizations, and the employees surveyed in these studies have identified some of the possible drivers of knowledge hiding to be: a lack of employee trust; poor employee incentives; employee retaliation; employee insecurity; the intentional withholding of knowledge; the workplace environment; a craving for competitive advantage over fellow staff members; and also, feelings of psychological ownership. This paper investigates the influence of servant leadership on knowledge hiding, and proposes a mediating variable: that of the influence of psychological ownership of knowledge on the relationship between servant leadership and knowledge hiding attitudes in staff within organizations. A model is therefore proposed to achieve this, since it could be argued that increased servant leadership, through the psychological ownership of knowledge, can have a positive effect on staff attitudes towards knowledge hiding, and can also be used to encourage them to share knowledge to improve their overall performances, and the competitive advantages of organizations. The proposed model can also be used to assist managers in developing strategies for motivating staff to become more committed to the visions of organizations, in order to improve the performances of both themselves and their organizations overall.